2022
DOI: 10.3390/su14095063
|View full text |Cite
|
Sign up to set email alerts
|

The Right to Inclusive Quality Education: Primary School Teachers’ Perceptions Based on the EPREPADI-1 Scale

Abstract: The following study aimed to describe the perception of primary education teachers regarding pupils who are discriminated against on the grounds of low functional performance. In this way, the EPREPADI-1 scale (primary education teachers’ perception of their training and professional practice in relation to pupils with disabilities) was applied with a purposive and non-probabilistic sampling aimed at teachers in the Region of Murcia, obtaining a sample with a confidence level of 95% and a sampling error of 5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
1
0
1
Order By: Relevance
“…Another concerning aspect, in which we concur with other studies [40][41], is the perceived inability reported by students to develop and advocate for inclusive practices. In this regard, they consider that they have limited competencies, skills, and methodological and organizational strategies to promote IE strategies, which aligns with [41].…”
Section: Students' Perceptions Of Inclusive Educationsupporting
confidence: 91%
See 1 more Smart Citation
“…Another concerning aspect, in which we concur with other studies [40][41], is the perceived inability reported by students to develop and advocate for inclusive practices. In this regard, they consider that they have limited competencies, skills, and methodological and organizational strategies to promote IE strategies, which aligns with [41].…”
Section: Students' Perceptions Of Inclusive Educationsupporting
confidence: 91%
“…They always consider the personal characteristics of the diagnosed student in terms of deficit or need. This perception of IE by students in training, which appears in numerous studies [39][40], focuses on individual differences, institutional barriers, and personalized attention [39]. It prevents the development of a comprehensive project that is the responsibility of the entire educational community, especially of the teaching staff, and involves providing educational support to all students in general [7].…”
Section: Students' Perceptions Of Inclusive Educationmentioning
confidence: 99%
“…;Díaz y Molina (2022) se debe generar un análisis sobre la formación inicial y continua, como este genera un impacto en el desarrollo profesional de los educandos. En tanto,Niño et al, (2019) los docentes deben mantener y fomentar el diálogo con los padres o tutores de cada alumno, porque la educación comienza en el hogar y los representantes legales están involucrados en el proceso educativo del niño.…”
unclassified